Unique Cerebrovascular Anomalies in Noonan Syndrome With RAF1 Mutation. (August 2014) - Zarate, Yuri A.; Lichty, Angie W.; Champion, Kristen J.; Clarkson, L. Kate; Holden, Kenton R.; Matheus, M. Gisele
Noonan syndrome is a common autosomal dominant neurodevelopmental disorder caused by gain-of-function germline mutations affecting components of the Ras-MAPK pathway. The authors present the case of a 6-year-old male with Noonan syndrome, Chiari malformation type I, shunted benign external hydrocephalus in infancy, and unique cerebrovascular changes. A de novo heterozygous change in the RAF1 gene was identified. The patient underwent brain magnetic resonance imaging, computed tomography angiography, and magnetic resonance angiography to further clarify the nature of his abnormal brain vasculature. The authors compared his findings to the few cases of Noonan syndrome reported with cerebrovascular pathology.